New poly(ether urethane)s based on lignin derived aromatic chemicals via A-B monomer approach: synthesis and characterization - Kuhire, Sachin S.; Avadhani, C. V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2015)
{omega-Hydroxyalkyleneoxy benzoyl azides were synthesized starting from lignin-derived phenolic acids (vanillic acid and syringic acid) and omega-haloalkanols (6-chlorohexanol and 11-bromoundecanol). These bio-derived A-B monomers were self-polycondensed to afford poly(ether urethane)s which exhibited reasonably high molecular weights (eta(inh) = 0.41-0.69 dL g(-1), and M-n
Keywords: A-B type monomer; Poly(ether urethane)s; Renewable resources; Self-polycondensation

Partially bio-based poly(amide imide)s by polycondensation of aromatic diacylhydrazides based on lignin-derived phenolic acids and aromatic dianhydrides: synthesis, characterization, and computational studies - Kuhire, Sachin S.; Sharma, Pragati; Chakrabarty, Suman; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Two new bio-based diacylhydrazide monomers, namely, 4,4-(propane-1,3-diylbis(oxy))bis(3-methoxybenzohydrazide) and 4,4-(propane-1,3-diylbis(oxy))bis(3,5-dimethoxybenzohydrazide) were synthesized starting from lignin-derived phenolic acids, namely, vanillic acid and syringic acid. A series of poly(amide imide)s was synthesized by polycondensation of these diacylhydrazide monomers with commercially available aromatic dianhydrides. Poly(amide imide)s showed inherent viscosity in the range 0.44-0.56 dLg(-1) and exhibited good solubility in organic solvents. Poly(amide imide)s could be cast into transparent, flexible, and tough films from their N,N-dimethylacetamide solutions. Poly(amide imide)s showed 10% weight loss in the temperature range 340-364 degrees C indicating their good thermal stability. Glass transition temperature (T-g) of poly(amide imides)s were measured by DSC and DMA which were in the range 201-223 degrees C and 214-248 degrees C, respectively. The T-g values of poly(amide imide)s were dependent on the number methoxy substituents on aromatic rings of diacylhydrazide monomers. Molecular dynamics simulation studies revealed that chain rigidity is the dominant factor for observed trends in T-g. (c) 2017 Wiley Periodicals, Inc.
Keywords: Biobased Polymers; Computational studies; Glass-transaction temperature; lignin; Monomers; Plant oils; Polyimide; Reneable resources; Renewable resources; Step-growth polymers; structure-property relations; Sustanaible Polymers; Thermal night; Thermosetting resins; Vanillin

Synthesis and characterization of partially bio-based polyimides based on biphenylene-containing diisocyanate derived from vanillic acid - Kuhire, Sachin S.; Ichake, Amol B.; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (European Polymer JOurnal, 2018)
A new bio-based biphenylene-containing diisocyanate, namely, 5,5'-diisocyanato-2,2',3,3'-tetramethoxy-1,1'-biphenyl (BDI) was synthesized starting from vanillic acid - a lignin-derived phenolic acid. A series of new partially bio-based polyimides was prepared by polycondensation of BDI with five commercially available aromatic dianhydrides. Polyimides exhibited good solubility in organic solvents and medium molecular weights (Mn (GPC, polystyrene standard) = 25,100-32,200 g mol(-1)). Polyimides showed good thermal stability with 10% degradation temperature and glass transition temperature in the range 459-473 degrees C and 262-329 degrees C, respectively.

Aromatic polycarbonates bearing pendant maleimide groups via functional monomer approach: synthesis and characterization - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Rajamohanan, P. R.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2019)
A new bisphenol containing pendant maleimide group, viz., 4, 4'-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA), was synthesized starting from commercially available 4, 4'-bis (4-hydroxyphenyl) pentanoic acid. Aromatic (co)polycarbonates possessing pendant maleimide groups were synthesized by solution polycondensation of BPA-MA or varying mixtures of BPA-MA and bisphenol-A (BPA) with triphosgene in dry dichloromethane in the presence of triethylamine as a base. Inherent viscosities and number average molecular weights of (co)polycarbonates were in the range 0.46-0.66 dL/g and 24,600-36,700, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)polycarbonates. (Co)polycarbonates were characterized using FT-IR, H-1 NMR, C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolycarbonate containing pendant maleimide groups was carried out quantitatively using thiol-maleimide Michael addition reaction with two thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol. Additionally, it was demonstrated that copolycarbonate containing pendant maleimide groups could be used to form insoluble cross-linked gel by reaction with a multifunctional thiol cross-linker, namely, pentaerythritol tetrakis(3-mercaptopropionate).
Keywords: Aromatic polycarbonate; Cross-linking; maleimide group; Thiol-maleimide reaction; Triphosgene

Design and synthesis of aromatic polyesters bearing pendant clickable maleimide groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Jadhav, Uday A.; Dhanmane, Sushilkumar A.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
A bisphenol bearing pendant maleimide group, namely, N-maleimidoethyl-3, 3-bis(4-hydroxyphenyl)-1-isobenzopyrrolidone (PPH-MA) was synthesized starting from phenolphthalein. Aromatic (co)polyesters bearing pendant maleimide groups were synthesized from PPH-MA and aromatic diacid chlorides, namely, isophthaloyl chloride (IPC), terephthaloyl chloride (TPC), and 50:50 mol % mixture of IPC and TPC by low temperature solution polycondensation technique. Copolyesters were also synthesized by polycondensation of different molar proportions of PPH-MA and bisphenol A with IPC. Inherent viscosities and number-average molecular weights of aromatic (co)polyesters were in the range of 0.52-0.97 dL/g and 20,200-32,800 g/mol, respectively indicating formation of medium to reasonably high-molecular-weight polymers. C-13 NMR spectral analysis of copolyesters revealed the formation of random copolymers. The 10% weight loss temperature of (co)polyesters was found in the range 470-484 degrees C, indicating their good thermal stability. A selected aromatic polyester bearing pendant maleimide groups was chemically modified via thiol-maleimide Michael addition reaction with two representative thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol to yield post-modified polymers in a quantitative manner. Additionally, it was demonstrated that polyester containing pendant maleimide groups could be used to form insoluble crosslinked gel in the presence of a multifunctional thiol crosslinker. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 630-640
Keywords: crosslinking; maleimide group; modification; polyesters; thiol-maleimide

Partially bio-based aromatic poly(ether sulfone)s bearing pendant furyl groups: synthesis, characterization and thermo-reversible cross-linking with a bismaleimide - Nagane, Samadhan S.; Kuhire, Sachin S.; Mane, Shivshankar R.; Wadgaonkar, Prakash P. (Polymer Chemistry, 2019)
A fully bio-based bisphenol bearing pendant furyl group, viz., 4,4'-(furan-2-ylmethylene) bis(2-methoxyphenol) (BPF) was synthesized by base-catalyzed condensation of furfural with guaiacol. New partially bio-based (co) poly(ether sulfone) s bearing pendant furyl groups were synthesized via aromatic nucleophilic substitution polycondensation of BPF and various mixtures of BPF and bisphenol-A with bis(4-fluorophenyl) sulfone in N, N-dimethylacetamide as a solvent. (Co) poly(ether sulfone) s showed inherent viscosities in the range 0.92-1.47 dL g(-1) and number average molecular weights ((M-n) over bar), obtained from GPC, were in the range 91 300-131 000 g mol(-1). (Co) poly(ether sulfone) s could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether sulfone)s showed 10% weight loss in the temperature range 431-481 degrees C and DSC showed T-g in the range 179-190 degrees C. Tensile strength, Young's modulus and elongation at break, obtained from tensile testing of (co) poly(ether sulfone) s containing pendant furyl groups, were in the range 76.7-83.8 MPa, 1.02-1.18 GPa and 21.4-89.7%, respectively. Most interestingly, pendant furyl groups in (co) poly(ether sulfone) s provide reactive sites for click modification and cross-linking via Diels-Alder reaction with maleimides and bismaleimides, respectively. Crosslinked (co) poly(ether sulfone) was prepared via Diels-Alder reaction of a representative (co) poly(ether sulfone) containing pendant furyl groups with 1,1'-(methylenedi-1,4-phenylene) bismaleimide (BMI) at 60 degrees C. The formation of cross-linked poly(ether sulfone) was demonstrated by gelation tests, solubility tests and DSC. The cross-linked copoly(ether sulfone) prepared using BMI showed enhanced tensile strength and Young's modulus compared to parent copoly(ether sulfone) and was recycled two times with retention of mechanical properties.

Partially bio-based furyl-functionalized organosoluble poly(ether ether ketone)s - Kuhire, Sachin S.; Talanikar, Aniket A.; Tawade, V, Bhausaheb; Nagane, Samadhan S.; Wadgaonkar, Prakash P. (Polymer International, 2021)
A new series of partially bio-based (co)poly(ether ether ketone)s bearing pendent furyl groups was synthesized by nucleophilic aromatic substitution polycondensation of varying molar proportions of 4,4 `-(furan-2-ylmethylene)bis(2-methoxyphenol) and bisphenol-A with 4,4 `-difluorobenzophenone. The chemical structures, compositions and random nature of (co)poly(ether ether ketone)s were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of the (co)poly(ether ether ketone)s were in the range 0.74-2.90 dL g(-1) and 33 500-46 300 g mol(-1), respectively, indicating the formation of reasonably high molecular weight polymers. (Co)poly(ether ether ketone)s were readily soluble in common organic solvents and could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether ether ketone)s exhibited 10% weight loss and glass transition temperatures in the range 429-464 and 152-156 degrees C, respectively. A representative copoly(ether ether ketone) was crosslinked with 1,1 `-(methylenedi-1,4-phenylene)bismaleimide via Diels-Alder reaction to form a crosslinked polymer which showed improved mechanical properties and was recycled twice without significant loss of mechanical properties. Diels-Alder/retro Diels-Alder reaction was demonstrated by studies of sol-gel transformation, solubility tests, DSC and stress-strain measurements. (c) 2020 Society of Chemical Industry
Keywords: aromatic poly(ether ether ketone)s; bio-based; crosslinking; Diels-Alder reaction; pendent furyl groups

Synthesis, characterization and UV-crosslinking of aromatic (Co)polycarbonates bearing pendant azido groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Talanikar, Aniket A.; Lochab, Bimlesh; Wadgaonkar, Prakash P. (ChemistrySelect, 2022)
A new series of (co)polycarbonates bearing pendent azido groups was synthesized by polycondensation of varying molar proportions of 4, 4'-(5-azidopentane-2, 2-diyl) diphenol and bisphenol-A with triphosgene. The chemical structures, compositions and random nature of (co)polycarbonates were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of (co)polycarbonates were in the range 0.63-0.77 dL g(-1) and 35,400-43,400 g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. (Co)polycarbonates could be cast into tough, transparent and flexible films from chloroform solutions. (Co)polycarbonates were further characterized using IR spectroscopy, XRD, TGA and DSC. The thermal crosslinking of (co)polycarbonates bearing pendant azido groups was studied by DSC analysis. Independently, (co)polycarbonates bearing pendant azido groups were exposed to UV irradiation at wavelength of 254 nm and decomposition reaction of azido groups was monitored by FT-IR spectroscopy. The complete decomposition of azido groups was observed with exposure time of 30 min. The formed cross-linked (co)polycarbonates exhibited improved % char yield values compared to parent (co)polycarbonates. The measurement of mechanical properties of representative crosslinked (co)polycarbonates indicated increase in tensile strength and Young's modulus and decrease in % elongation compared to corresponding parent linear (co)polycarbonates.
Keywords: Aromatic polycarbonate; Pendant azido group; solution polycondensation; Triphosgene; UV-crosslinking